Introduction: Teaching Black Lives Matter - Austin, Paula; Cardwell, Erica; Kennedy, Christopher; Spencer, Robyn (Radical Teacher, 2016)
An introduction to Radical Teacher, Issue 106: Teaching Black Lives Matter. This issue brings together a diverse collection of articles exploring educator’s responses, strategies, and stories on how #BlackLivesMatter has informed their teaching practice, the content of their courses, and their personal relationship to colleagues, family, friends, and self.